CT angiography-derived three-dimensional pulmonary vein topography is related to the outcome after cryoballoon ablation - Saal, Martin; Esser, Annika; Becker, Torsten; Stöckigt, Florian; Mohsen, Yazan; Horlitz, Marc; Haude, Michael; Rottländer, Dennis (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFollowing cryoballoon ablation, 20%–30% of the patients show recurrent atrial fibrillation (AF) in long-term follow-up as a consequence of incomplete circumferential ablation lines. Patient selection using computer tomography angiography (CTA)-derived parameters might be feasible to assign patients for cryoballoon ablation according to pulmonary vein (PV) anatomy and topography.MethodsWe aimed to analyze the impact of anatomical and topographic PV parameters on the procedural outcome of cryoballoon PVI using a retrospective analysis of 106 patients with paroxysmal AF and preprocedural CTA.ResultsClinical follow-up of the study cohort revealed 78 patients (73.6%, PVI success group) without and 28 patients (26.4%, PVI failure group) with recurrent AF 12 months after cryoablation. Anatomical measurements such as PV diameter, PV area, PV perimeter, or PV eccentricity were not associated with procedural success. The number of occlusion attempts in the right inferior PV was significantly higher in the PVI failure group indicating a technical more complex balloon occlusion. The septum angle α (septum–PV) was significantly lower in the superior PVs of the PVI failure group indicating a direct relation of transseptal puncture site to procedural success. Furthermore, orifice angle β (PV orifice–PV course) was increased and intra-atrial angle γ (septum–PV course) was decreased in the inferior PVs of the PVI failure group.ConclusionPatient selection using CTA prior to cryoballoon ablation might influence the procedural success of cryoballoon PVI. While PV anatomy in regard to vein size and shape was not associated with procedural outcome, septum, orifice, and intra-atrial angulation were related to procedural success.